An empirical study on fiscal sustainability in Malaysia - Abdullah, Hussin; Mohd Mustafa, Muszafarshah; Dahalan, Jauhari (Human Resource Management Academic Research Society, 2012)
Fiscal sustainability has become a prominent issue in developing countries, and fiscal sustainability assessments have become an increasingly demanded component of macroeconomic analysis. Unfortunately, there is no single basic source of information on fiscal sustainability.Country economists who are new to fiscal sustainability analysis could rely on sample work by other economists and could delve into scattered journal articles for the theoretical background.This paper focuses on a particular country: Malaysia. The main purpose of this paper is to monitor fiscal sustainability in Malaysia using empirical analysis, and see whether the fiscal sustainability indicators are consistent with the co-integration framework. We employ VAR analysis as it is simple to compute and easily automated. We show how it is possible to analyze a change of policy within a VAR framework. We also use a Multivariate Co-integration Test methodology to conduct inference about the co-integrating relationship between fiscal sustainability indicators and output (GDP). Empirical validation from the time series analysis finds that fiscal sustainability indicators and Gross domestic Product (GDP) are co-integrated, which provides some support for the position that Malaysia’s fiscal sustainability is sustainable in the long run in sampling period.This finding suggests that the Government should improve the presentation of sustainability of fiscal policy and develop the analysis, review the sustainability indicators, and strengthen the role of the long term estimates in the design of short term fiscal policy.